Pengembangan E – Modul Berbasis Socio Scientific Issues (SSI) Pada Materi Struktur Bumi dan Perkembangannya Untuk Mendukung Kemampuan Literasi Sains Peserta Didik SMP - Intan Alia Kusuma; Sjaifuddin Sjaifuddin; Lulu Tunjung Biru (UNIB Press, 2026)
This research is motivated by observational findings indicating low scientific literacy skills among junior high school students, as well as a lack of teaching materials and pedagogical approaches that have yet to achieve optimal effectiveness. Based on the analysis of these issues, this study aims to evaluate the product's validity and analyze student responses regarding the implementation of an e-module based on Socio-Scientific Issues (SSI) and its development, designed to stimulate scientific literacy. The research follows the Research and Development (R&D) method, utilizing the ADDIE development model, limited to the Analysis, Design, and Development stages. Instrument validity was tested using validation sheets from material experts, media experts, and practitioners. Subsequently, the implementation phase in a small-scale limited trial was conducted by employing questionnaire instruments to gather student responses. The validation results from material experts, media experts, and practitioners reached 90.4%, categorized as 'highly valid.' The student response validation result was 92%, falling into the 'excellent' category. Based on these findings, this SSI-based e-module is declared to have a very high level of feasibility for implementation as an instructional tool to optimize students' scientific literacy skills.